Anthropocentrism and Environmental Crisis in Hujan Novel by Tere Liye: An Ecocritical Study of Human-Induced Environmental Damage - Romdoni, Muhamad Rizky (Jurnal Pendidikan Makarios, 2024)
This study aims to reveal how human actions impact environmental damage as depicted in the novel Hujan by Tere Liye. The research design used a qualitative method, equipped with an ecocriticism theory of Anthropocentrism by Greg Garrard to explore the anthropocentrism in the novel. The results show; 1) The environmental damage: different kinds of environmental harm, including pollution, apocalypse, dwelling, and earth, with humans as the main cause and the impact that causes the ecosystem damage which eventually leads to extinction; 2) The environmental abuse: the role of humans in the destruction of the environment is reflected in the actions of destroying nature carried out by humans on the basis of the anthropocentrism paradigm; 3) The ecological ethics: the novel highlights the critical need for adhering to environmental wisdom, which includes maintaining harmony with nature, adopting sustainable practices, and considering long-term consequences of human actions.environmental values are embodied in the novel following the principles of environmental ethics.